A comparative study of choroidal thickness and pigment epithelial detachment in acute and chronic central serous chorioretinopathy in Nepalese patients - Subash Bhatta; Nayana Pant; Suresh Raj Pant (PLoS ONE, 2025)
Background To study the significance and correlation of choroidal and retinal pigment epithelial changes with disease activity in Central Serous Chorioretinopathy (CSCR) eyes. Methods This was a retrospective analysis of clinical records and optical coherence tomography (OCT) images of CSCR cases presenting to a tertiary eye hospital in Nepal between October 2021 to November 2022. The study included 145 CSCR eyes from 132 cases compared with 290 eyes of 145 age- and sex-matched healthy volunteers. Chi square test, Paired T-test and Independent sample t-test were used for statistical analysis. Results Average subfoveal choroidal thickness (SFCT) of the CSCR eyes (453.13 um) and the fellow eyes (403.44 um) was significantly greater (p < 0.001) than that of the control group (372.29um). Notably, the eyes affected by CSCR also had significantly greater SFCT than fellow eyes (p < 0.01). No significant correlation was observed between subfoveal choroidal thickness (SFCT) and either central subfield macular thickness (CST) (p = 0.559) or pigment epithelial detachment (PED) (p = 0.145). Chronic CSCR eyes showed a significant association with PED (Chi-square test, p < 0.013), and a trend toward reduced CST and SFCT compared to acute eyes, as indicated by the independent t-tests ( p = 0.04 and p = 0.023, respectively). Flat and irregular PEDs were more common in chronic CSCR eyes compared to acute CSCR eyes (p = 0.027). Conclusions Increased SFCT and PED are significant pathophysiological markers in CSCR, exhibiting distinct variations between acute and chronic forms. However, the lack of a direct correlation of SFCT with CST and PED underscores the limitation of relying solely on SFCT to fully characterize choroidal changes in CSCR. Further exploration of additional OCT biomarkers may offer deeper insights into the complex pathophysiology of these changes, paving the way for enhanced understanding and more targeted therapeutic strategies.